Nanodrugs Detonate Lysosome Bombs - Xiang, Yuting; Li, Niansheng; Liu, Min; Chen, Qiaohui; Long, Xingyu; Yang, Yuqi; Xiao, Zuoxiu; Huang, Jia; Wang, Xiaoyuan; Yang, Yunrong; Zhang, Jinping; Liu, Chong; et al. (Frontiers in Pharmacology, 2022)
Cancer cell lysosomes contain various hydrolases and undegraded substrates that are highly corrosive enough to destroy cancer cells. Nevertheless, many traditional small molecule drugs targeting lysosomes have strong side effects because they cannot effectively differentiate between normal cells and cancer cells. Most lysosome-based research is limited to how to induce mild LMPs to help anticancer drugs from lysosomal traps into the cancer cell plasm. In fact, lysosomes are especially like a powerful bomb. If lysosomal membrane permeabilization (LMP) can be selectively induced in cancer cells, it will have high-efficiency anti-cancer effects and extremely low side effects. Nanodrugs can be specifically designed to selectively induce LMP in cancer cells according to the differences between cancer cells and tumor cells thanks to the diverse and combinable properties of nanodrugs. In recent years, great progress has been made in the study of nanodrugs-induced LMP, but related reviews are rarely reported. Herein, we first comprehensively summarize the advances of nanodrugs-induced LMP. According to the differences in the strategies adopted by LMP, these nanodrugs-induced LMP are mainly divided into nanoparticles aggregation-induced LMP, chemodynamic therapy (CDT)-induced LMPs and d magnetic field induced LMP. Finally, we also analyze the prospect of nanodrugs-induced LMP and the problems to be overcome. We believe this review provides a unique perspective and inspiration for designing lysosome-targeted drugs.